Gender and Development Integration in the Curriculum towards Inclusive Education - Boholano, Helen B.; Revita, Ike; Villaver, Debie Joyce B. (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
This study investigates how students' attitudes regarding gender roles, academic success in STEM disciplines, and involvement in gender-related activism are affected by the inclusion of gender in development courses. In order to provide a thorough understanding of the consequences of gender integration, the study uses a mixed-methods research design that draws on feminist theory, social learning theory, and critical pedagogy. While qualitative analysis focuses on students' participation in gender-related activity, quantitative analysis looks at changes in students' perceptions toward gender roles and academic success in STEM disciplines. The results demonstrate the beneficial effects of gender integration on students' perceptions of gender roles, with inclusive curricula challenging prevailing prejudices and enabling learners to adopt more equitable viewpoints. Students are shown to be motivated to participate in gender-related activities by gender integration. An inclusive curriculum encourages active engagement and helps to bring about social change through bringing attention to issues, advancing social justice, and giving students the tools they need to confront gender inequality. Overall, this study emphasizes how important it is to integrate gender perspectives into the classroom in order to establish welcoming and equal learning environments. The findings underscore the necessity to include gender-related concerns in educational policies and practices and add to the body of research on gender integration. Society may work toward gender equality and enable people to be change agents by adopting inclusive education.